Giant fibroadenoma of the breast: A rare case in a mature woman. (2019) - Meng, Xiangyue; Yamanouchi, Kosho; Kuba, Sayaka; Sakimura, Chika; Morita, Michi; Matsuguma, Kunihito; Kanetaka, Kengo; Takatsuki, Mitsuhisa; Abe, Kuniko; Eguchi, Susumu
Highlights: We experienced giant fibroadenoma of breast, a rare case in a mature woman. We suspected a malignant tumor, due to the size and ulceration and bleeding. Total mastectomy and skin grafting were needed for complete resection. An early diagnosis and treatment could prevent total mastectomy. Abstract: Introduction: Fibroadenomas are common benign lesions of the breast that are usually found young patients. Giant fibroadenomas are uncommon benign lesions, defined as fibroadenomas of >5 cm in size, which are usually found in patients of less than 20 years of age. Presentation of case: A 39-year-old premenopausal woman presented with a right breast tumor that had rapidly increased in size and which showed ulceration and bleeding. Needle biopsy showed mixed connective tissue and an epithelial tumor without a leaf-like pattern, but indeterminate. Total mastectomy and skin grafting were performed. Histopathology confirmed the diagnosis of giant fibroadenoma. Discussion: In comparison to all previous reports on patients with giant fibroadenoma, this patient was relatively old and the etiology was unknown. Although rare, an appropriate therapeutic strategy should be decided according to the results of a histopathological examination. Conclusion: Early treatment could allow breast preserving surgery and patients should be recommended to undergo reexamination with awareness of progression.